Conceptualizing Kirchnerismo - Peruzzotti, Enrique (PARTECIPAZIONE E CONFLITTO, 2017)
What is the nature of kirchnerismo? The experience of the period encompassed by the presidencies of Nestor and Cristina Kirchner have generated greater controversy regarding its characterization. The article critically reviews the analysis that Ernesto Laclau and Guillermo O’Donnell made of kirchnerismo through their respective conceptual models of populism and delegative democracy.